2019
DOI: 10.3892/ijo.2019.4792
|View full text |Cite
|
Sign up to set email alerts
|

Serum bradykinin levels as a diagnostic marker in cervical cancer with a potential mechanism to promote VEGF expression via BDKRB2

Abstract: Bradykinin (BK) is one of the kinin peptides and preferentially binds to bradykinin B2 receptor (BDKRB2). A recent study indicated that BK played an important role in the occurrence and progression of cancer. In this study, we evaluated the serum BK levels in 130 cervical cancer (CC) cases (including 65 cases with pre- and post-surgery paired samples, another 65 cases with only pre-surgery samples), 35 cervical intraepithelial neoplasia (CIN) cases (pre- and post-surgery paired) and 35 control cases. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
(41 reference statements)
0
17
0
1
Order By: Relevance
“…Notably, according to their nearby genes, the present study was also able to identify a few tumor-associated lncRNAs altered in BC. ENST00000562848, ENST00000587187, ENST00000398878, ENST00000421206, ENST00000443576 and ENST00000562393 are spliced from the neighboring areas of HOXC6 ( 58 ), UHRF1 ( 59 ), SULT1A3 ( 60 ), GRK5 ( 61 ), STARD13 ( 62 ) and BDKRB2 ( 63 ), which plays a critical role in malignant proliferation, migration and metastasis. Overall, these findings indicated that these lncRNAs are associated with a diverse range of different types of cancer, thereby emphasizing the accuracy of the sequencing data in the present study, and indicating the potential critical role of these lncRNAs in the development of BC as well.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, according to their nearby genes, the present study was also able to identify a few tumor-associated lncRNAs altered in BC. ENST00000562848, ENST00000587187, ENST00000398878, ENST00000421206, ENST00000443576 and ENST00000562393 are spliced from the neighboring areas of HOXC6 ( 58 ), UHRF1 ( 59 ), SULT1A3 ( 60 ), GRK5 ( 61 ), STARD13 ( 62 ) and BDKRB2 ( 63 ), which plays a critical role in malignant proliferation, migration and metastasis. Overall, these findings indicated that these lncRNAs are associated with a diverse range of different types of cancer, thereby emphasizing the accuracy of the sequencing data in the present study, and indicating the potential critical role of these lncRNAs in the development of BC as well.…”
Section: Discussionmentioning
confidence: 99%
“…Of the two, B1R expression is considered the more ideal target because of its low expression in normal tissues. B1R activation has been shown to potentiate malignant behaviors by inducing cell proliferation, migration, and angiogenesis [ 59 , 60 , 61 ]. The pro-inflammatory effect of B1R activation can modulate the tumor microenvironment, priming for distant metastasis [ 62 ].…”
Section: Kinin Receptors In Diseasementioning
confidence: 99%
“…In recent years, the incidence of CC has increased greatly in young women under the age of 35 [2]. Despite great advances in surgical and adjuvant therapy, the overall survival of CC patients, especially that of advanced patients, is still very poor [3]. At present, a Pap smear combined with an HPV test has been used for the early screening of cervical lesions.…”
Section: Introductionmentioning
confidence: 99%
“…At present, a Pap smear combined with an HPV test has been used for the early screening of cervical lesions. However, the screening methods are invasive and costly, leading to lower screening coverage in China [3]. Previous studies have reported that the human papillomavirus (HPV) screening results have a relatively high false-positive rate and a relatively low specificity [4,5].…”
Section: Introductionmentioning
confidence: 99%